Association of Microalbuminuria with Severity of Coronary Artery Disease in Diabetic Patients: A Cross-Sectional Study - Khan, Md. Mizanur Rahman; Alam, Md. Rezaul; Jahan, Ferdous; Islam, Kazi Mohammad Kamrul; Imam, Hasan; Jahan, Mahfuja (Archives of Clinical and Biomedical Research, 2025)
Introduction: Coronary artery disease (CAD) remains one of the leading causes of morbidity and mortality among individuals with type 2 diabetes mellitus (T2DM). Microalbuminuria, an early marker of endothelial dysfunction and renal damage, has emerged as a potential predictor of cardiovascular complications in diabetic patients. This study aimed to assess the association of microalbuminuria with the severity of coronary artery disease in diabetic patients. Methods: This cross-sectional analytical study was conducted at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from January 2024 to June 2024, involving 103 adult patients with type 2 diabetes mellitus who underwent elective coronary angiography. Statistical analysis was performed using SPSS software version 26.0. p-value <0.05 is considered statistically significant. Result: The severity of coronary artery disease (CAD) was notably greater in the microalbuminuric group, with 34.3% exhibiting triple-vessel disease, and only 9.0% showing no significant CAD (vs. 38.9% in the normoalbuminuric group; p < 0.001). Urinary albumin excretion increased with the number of vessels involved, indicating a strong positive correlation. Logistic regression analysis identified microalbuminuria (OR 3.92; p = 0.003), duration of diabetes (OR 1.13; p = 0.017), and HbA1c (OR 1.48; p = 0.031) as independent predictors of multivessel CAD. Additionally, patients with microalbuminuria had significantly lower left ventricular ejection fraction (49.8 ± 7.2% vs. 53.1 ± 6.3%; p = 0.038), suggesting greater cardiac dysfunction. Conclusion: This study demonstrates a significant association between microalbuminuria and the severity of coronary artery disease (CAD) in patients with type 2 diabetes mellitus. The presence of microalbuminuria correlated with longer diabetes duration, poorer glycemic control, reduced left ventricular ejection fraction, and increased incidence of multivessel CAD. These findings suggest that microalbuminuria may serve as an independent predictor of CAD severity and could be a valuable, cost-effective marker for early cardiovascular risk stratification in diabetic individuals.